2011
DOI: 10.1158/0008-5472.can-11-0640
|View full text |Cite
|
Sign up to set email alerts
|

FoxM1: A Master Regulator of Tumor Metastasis

Abstract: The FoxM1 transcription factor gene is over-expressed in cancer. Its expression is stimulated by oncogenic signaling pathways and reactive oxygen species. It is also a target of regulation by the tumor suppressor genes. The transcriptional activity of FoxM1 depends upon activation by the Cyclin/Cdks as well as Plk1. FoxM1 stimulates expression of several genes involved in the cell cycle progression. Moreover, it supports proliferation of tumor cells by stimulating expression of the antioxidant genes and reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
237
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(254 citation statements)
references
References 30 publications
11
237
1
Order By: Relevance
“…S4). FOXM1 is frequently associated with metastasis and patient survival in many types of cancers (28,29); it was also reported that FOXM1 activity was significantly increased in bladder cancers relative to normal bladder tissues and might have a prognostic value at the individual level (30). CCNB1, a downstream effector of FOXM1, is upregulated and is known to be a prognostic biomarker in many cancers (25)(26)(27).…”
Section: Discussionmentioning
confidence: 98%
“…S4). FOXM1 is frequently associated with metastasis and patient survival in many types of cancers (28,29); it was also reported that FOXM1 activity was significantly increased in bladder cancers relative to normal bladder tissues and might have a prognostic value at the individual level (30). CCNB1, a downstream effector of FOXM1, is upregulated and is known to be a prognostic biomarker in many cancers (25)(26)(27).…”
Section: Discussionmentioning
confidence: 98%
“…Accumulating evidence shows that activation of FOXM1 is associated with the development of human cancers (33)(34)(35). FOXM1 is a FOX transcription factor that regulates a number of cell cycle regulators (33,34,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 is a FOX transcription factor that regulates a number of cell cycle regulators (33,34,36,37). Several studies have shown that FOXM1 is overexpressed in tumors including lung, liver and breast cancers and is associated with prognosis (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) trigger expression of FoxM1 and interestingly, FoxM1 also triggers expression of ROS scavengers such as Superoxide Dismutase (SOD), Catalase [6,7]. Overexpression of FoxM1 renders cancer cells resistance to ROSmediated cell death.…”
Section: Introductionmentioning
confidence: 99%